Clinical Symptoms, Imaging Features and Cyst Distribution in the Cerebrospinal Fluid Compartments in Patients with Extraparenchymal Neurocysticercosis - Bazan, Rodrigo [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Luvizutto, Gustavo Jose [UNESP]; Carvalho Nunes, Helio Rubens de [UNESP]; Odashima, Newton Satoru; Santos, Antonio Carlos dos; Elias Junior, Jorge; Zanini, Marco Antonio [UNESP]; Fleury, Agnes; Takayanagui, Osvaldo Massaiti (Public Library Science, 2016)
Extraparenchymal neurocysticercosis has an aggressive course because cysts in the cerebrospinal fluid compartments induce acute inflammatory reactions. The relationships between symptoms, imaging findings, lesion type and location remain poorly understood. In this retrospective clinical records-based study, we describe the clinical symptoms, magnetic resonance imaging features, and cyst distribution in the CSF compartments of 36 patients with extraparenchymal neurocysticercosis. Patients were recruited between 1995 and 2010 and median follow up was 38 months. During all the follow up time we found that 75% (27/36) of the patients had symptoms related to raised intracranial pressure sometime, 72.2% (26/36) cysticercotic meningitis, 61.1% (22/36) seizures, and 50.0% (18/36) headaches unrelated to intracranial pressure. Regarding lesion types, 77.8% (28/36) of patients presented with grape-like cysts, 22.2% (8/36) giant cysts, and 61.1% (22/36) contrast-enhancing lesions. Hydrocephalus occurred in 72.2% (26/36) of patients during the follow-up period. All patients had cysts in the subarachnoid space and 41.7% (15/36) had at least one cyst in some ventricle. Cysts were predominantly located in the posterior fossa (31 patients) and supratentorial basal cisterns (19 patients). The fourth ventricle was the main compromised ventricle (10 patients). Spinal cysts were more frequent than previously reported (11.1%, 4/36). Our findings are useful for both diagnosis and treatment selection in patients with neurocysticercosis.